Determinants of the Flowchart Use by Registered Nurses and Associates in the Kasa-vubu Health Zone in Kinshasa, Democratic Republic of the Congo - , Oscar Kolnziam Nsutier, Désiré L. Nsobani, Tshiama Claudine, Deborah Mujinga Tshimungu, Jacques Murazini Kanika, Judith Gegeso Scherpes, Gédéon Ngiala Bongo (Archives of Current Research International, 2019)
Aims: The aims of this research was to identify the main determinants (factors) that contribute to the low flowchart use registered nurses in Kasa-Vubu Health Zone, and to verify the existence of a relationship between the studied factors and the socio-demographic characteristics of the respondents. Study Design: This analytical study with a correlational estimate aims to explore the relationships between variables related to intention and seeks to determine whether the variables involved are associated with facts. Place and Duration of the Study: This survey was carried out in the health facilities of Kasa-vubu health zone between May and June 2017. Methods: A questionnaire was used to collect data thru a structured interview. A pre-test was conducted in Bandalungwa health zone in order to provide quality care while using the flowchart. The Likert-type scale with seven choices was used in the design of different items. The sample size was established based on the number of participants per predictor variable in order to meet the statistical power in a multiple regression analysis. After calculation, the sample size was 105 respondents. The target study population was registered nurses, assistant registered Nurses and the executive nurses who use the flowchart during clinical consultation within their respective health centre including all the health centres in the aforementioned health zone. Data analysis was performed using SPSS version 20 software and the p-value <0.05 was considered to be significant whereby descriptive statistics and correlation of Pearson were used. For ethical reasons, the consent of the respondent was needed. Results: The analysis showed that 60% of the respondents were under 40 years of age, 50.5% were married, 80% had more than 5 years of service and 89.5% had a graduate degree. However, 59.0% were executive nurses. In addition, there is a statistically significant association between the use of the flowchart and motivation (p=0.014), the importance given by registered nurses and executive nurses in the therapeutic management of patients (p=0.001). Moreover, there is a statistically significant association between the flowchart systematic use and the education level during patient management (p=0.000). Last, there is an association between the flowchart systematic use and the importance given to facilitating and/or detrimental factors (p=0.001). Conclusion: The socio-demographic parameters, factors related to the importance given to facilitating and/or detrimental factors and motivational factors significantly influence the systematic use of the flowchart in the therapeutic management of patients in the Health zone of Kasa-vubu. Yet, key determinants, which favor the low use of the flowchart by nurses of Kasa-vubu health zone, were identified. Hence, this would draw the attention of decision-makers for a better improvement of the health system in order to have a better patient management in different health zones of Kinshasa in DRC.